2019
DOI: 10.1016/j.yjmcc.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain induces a pro-fibrotic phenotype in human mitral valvular interstitial cells through RhoC/ROCK/MRTF-A and Erk1/2 signaling pathways

Abstract: The mitral valve is a complex multilayered structure populated by fibroblast-like cells, valvular interstitial cells (VIC) which are embedded in an extracellular matrix (ECM) scaffold and are submitted to the mechanical deformations affecting valve at each heartbeat, for an average of 40 million times per year. Myxomatous mitral valve (MMV) is the most frequent heart valve disease characterized by disruption of several valvular structures due to alterations of their ECM preventing the complete closure of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…50 Another study demonstrated that mechanical strain induced the nuclear translocation of MRTF-A and a pro-fibrotic phenotype in human mitral valvular interstitial cells. 51 A recent study revealed that NP cells in stiff substrate appeared spread and fibrotic shape opposed to the round shape in soft matrix. 52 In addition, matrix stiffness increased nu- The RhoA/ROCK pathway is known to act as a prominent player in mechanical signals and remodelling of the actomyosin F I G U R E 5 Distinct effects of myosin IIA or IIB knockdown on compression stress-induced human NP cells senescence.…”
Section: Discussionmentioning
confidence: 99%
“…50 Another study demonstrated that mechanical strain induced the nuclear translocation of MRTF-A and a pro-fibrotic phenotype in human mitral valvular interstitial cells. 51 A recent study revealed that NP cells in stiff substrate appeared spread and fibrotic shape opposed to the round shape in soft matrix. 52 In addition, matrix stiffness increased nu- The RhoA/ROCK pathway is known to act as a prominent player in mechanical signals and remodelling of the actomyosin F I G U R E 5 Distinct effects of myosin IIA or IIB knockdown on compression stress-induced human NP cells senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The genome profile stability serves a crucial role in the maintenance of human health. Emerging evidence has indicated that the dysregulation of gene expression occurs in multiple diseases, such as cardiovascular disease ( 1 ), Parkinson's disease ( 2 ) and malignant tumors ( 3 , 4 ). Colorectal cancer (CRC) is a common malignant disease of the gastrointestinal tract; the incidence and mortality of CRC has been steadily declining for the past two decades ( 5 ), with an exception of younger adults (<50 years), which is possibly related to an increase in cancer screening and improved therapeutic modalities ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mechanical stretching increased the amount of CTGF secretion in anterior cruciate ligamentderived cells (Miyake et al, 2011), indicating that CTGF is a mechano-sensitive molecule. Blomme et al reported that valvular interstitial cells showed the significant upregulation of CTGF at 1.15 Hz (heart frequency) and 14% elongation mechanical stretch, which was promoted through RhoC and MEK/Erk signaling pathways (Blomme et al, 2019). Additionally, in our previous study, we found that pathological cyclic stretch induces vascular remodeling by promoting VSMC proliferation via the miR-19b-3p/CTGF pathway (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 50%